Identification and Assessment of Factors Affecting the Implementation of Beyond Activity-Based Costing System (BABCS) in Public Organizations of Kurdistan Region - Bakir Mahmud, Ibrahim; Zeynali, Mehdi; Pourkarim, Yaghoub; Mohammadi, Ahmad (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2023)
Objective: The purpose of this study is to identify and assess the factors influencing the implementation of the Beyond Activity-Based Costing System (BABCS) in public organizations of the Kurdistan region.Methodology: This research is applied in aim and mixed (qualitative-quantitative) in nature, utilizing interviews and researcher-made questionnaires. The statistical population includes managers, experts, and scholars in the field of the study.Findings: According to the perspectives of the statistical population, for the implementation of the BABCS system in the public organizations of the Kurdistan region, seven categories of factors are influential, including organizational-behavioral, technical, economic, design and execution, legal, external, and policy factors. The assessment of these factors in the current situation revealed that only the "legal factors" are relatively adequate, thus indicating that the conditions for implementing BABCS in public organizations of the Kurdistan region are not optimal. Additionally, regarding the potential for implementing BABCS in these organizations, all dimensions showed a positive status, with organizational-behavioral factors having a higher potential to aid the implementation of BABCS. Overall, the potential for employing BABCS in the public organizations of the Kurdistan region is currently in a relatively good state (scored 3.13 out of 5), and by overcoming barriers, this potential could be utilized.Conclusion: The BABCS method, which is critically needed in the public organizations of the Kurdistan region, can be implemented; as Kurdistan, with its recent advancements in various fields and the trend towards the development of public and semi-public organizations, urgently requires efficient and modern methods in the financial, managerial, and organizational arenas to achieve fruitful outcomes.